Altitudinal bird migration in North America - Boyle, W. Alice (My University, 2017)
Altitudinal bird migration involves annual seasonal movements up and down elevational gradients. Despite the fact that species from montane avifaunas worldwide engage in altitudinal migration, the patterns, causes, and prevalence of these movements are poorly understood. This is particularly true in North America where the overwhelming majority of avian migration research has focused on obligate, long-distance, temperate-tropical movements. Elsewhere in the world, most altitudinal migrants are partial migrants, making downhill movements to nonbreeding areas. However, spatial and temporal patterns, the prevalence and predictability of migration at individual and population levels, and the ultimate ecological factors selecting for movement behavior vary considerably among taxa and regions. I conducted a systematic survey of the evidence for altitudinal migration to fill gaps in our understanding of this behavior among the landbirds of North America and Hawaii. Altitudinal migration was as prevalent as in other avifaunas, occurring in >20% of continental North American and nearly 30% of Hawaiian species. Of the species wintering within the USA and Canada, similar to 30% engage in altitudinal migrations. Altitudinal migrants are far more common in the West, are taxonomically and ecologically diverse, and North American species exhibit patterns similar to altitudinal migrants elsewhere in the world. Because altitudinal migration systems are relatively tractable, they present excellent opportunities for testing hypotheses regarding migration generally. Altitudinal migration has likely been overlooked in North America due to contingency in the history of ornithological research. Our need to understand the patterns and causes of altitudinal migrations has never been greater due to emerging environmental threats to montane systems.
Citation: Boyle, W. A. (2017). Altitudinal bird migration in North America. Auk, 134(2), 443-465. doi:10.1642/auk-16-228.1
Keywords: Alpine; Altitudinal Movements; Elevational Migration; Facultative; Migration; High Elevation